Pertanggungjawaban Perawat sebagai Vaksinator dalam Menyuntikan Vaksin yang Menimbulkan Kerugian Dihubungkan dengan Undang-Undang Nomor 38 Tahun 2014 tentang Keperawatan - Raden Aura Galuh Rheina Wijaya; M. Faiz Mufidi (Bandung Conference Series: Law Studies, 2023)
Abstract. In an effort to restore world conditions to pre-pandemic conditions, vaccination programs have been carried out by governments around the world, including Indonesia. Researchers in various fields are finding solutions to tackle the global health challenge of Covid-19. The outbreak of SARS CoV 2 among humans makes it the third zoonotic virus to jump from animals to humans after SARS CoV and MERS-CoV. The vaccination program is considered the key to ending the pandemic because it can be used to reduce morbidity and mortality rates and form herd immunity against the Covid-19 virus. However, the journey for the vaccine to be well received and distributed to the wider community currently requires a longer process because there are still pros and cons to vaccination. However, since the development of the first Covid-19 vaccine, people have been reluctant to get vaccinated because they are worried about its safety and effectiveness. One of the cases related to safety and effectiveness is the case of injecting an empty vaccine that occurred at a private school in the Pluit area, Penjaringan, North Jakarta. Law Number 38 of 2014 concerning Nursing provides an understanding of nurses which explains that a nurse is someone who has completed higher education and graduated from domestic and foreign universities in the field of nursing whose standards are recognized by the government in accordance with applicable regulations. Meanwhile, due to the negligence of the nurse, the victim suffered a loss. The purpose of this study was to determine the responsibility of nurses who practice circumcision which harms patients in terms of Law Number 38 of 2014 concerning Nursing and to determine the legal consequences for nurses as vaccinators linked to Law Number 38 of 2014 concerning Nursing. The approach method used is normative juridical, the research specifications in this study are descriptive analytical. The data collection technique in this research is literature study and the analytical method in this study uses qualitative analysis methods. Then the result was obtained that there was a negligence committed by the nurse. The nurse's actions are included in the act against the law and the nurse must be responsible for these actionsKeywords-Child Trafficking and Sexual Exploitation, Protection of Human Rights, Accountability Abstrak. Dalam upaya mengembalikan kondisi dunia sebagaimana sebelum pandemi, telah diusung program vaksinasi oleh pemerintah di seluruh dunia, termasuk Indonesia. Para peneliti di berbagai bidang menemukan solusi untuk mengatasi tantangan kesehatan global Covid-19. Mewabahnya SARS CoV 2 di antara manusia menjadikannya sebagai virus zoonosis ketiga yang berpindah dari hewan ke manusia setelah SARS CoV dan MERS-CoV. Program vaksinasi dianggap sebagai kunci dalam mengakhiri pandemi karena dapat digunakan dalam rangka mengurangi angka morbiditas dan mortalitas serta membentuk kekebalan kelompok terhadap virus Covid-19. Namun, perjalanan vaksin hingga diterima dengan baik dan didistribusikan kepada masyarakat luas saat ini membutuhkan proses yang lebih panjang karena masih terdapat pro dan kontra terhadap vaksinasi. Namun, sejak pengembangan vaksin Covid-19 pertama, masyarakat enggan mengikuti vaksinasi karena khawatir akan keamanan dan efektivitasnya. Salah satu kasus yang berkaitan dengan keamanan dan efektivitas adalah kasus penyuntikkan vaksin kosong ini terjadi di suatu sekolah swasta kawasan Pluit, Penjaringan, Jakarta Utara. Undang-Undang Nomor 38 tahun 2014 tentang Keperawatan memberikan pengertian mengenai perawat yang menjelaskan bahwa Perawat adalah seorang yang telah selesai dalam menempuh pendidikan tinggi serta lulus pada perguruan tinggi didalam negeri maupun diluar negeri di bidang keperawatan yang standarnya diakui oleh pemerintah sesuai dengan ketentuan yang berlaku. Sementara akibat kelalaian perawat, korban mengalami kerugian. Tujuan penelitian ini adalah untuk mengetahui pertanggungjawaban perawat yang melakukan praktik khitan yang merugikan pasien ditinjau dari Undang-Undang Nomor 38 Tahun 2014 Tentang Keperawatan serta untuk mengetahui akibat hukum terhadap perawat sebagai vaksinator dihubungkan dengan Undang-Undang Nomor 38 Tahun 2014 tentang Keperawatan. Metode pendekatan yang digunakan adalah yuridis normatif, spesifikasi penelitian dalam penelitian ini bersifat deskriptif analitis, Teknik pengumpulan data dalam penelitian ini studi kepustakaan serta metode analisis dalam penelitian ini menggunakan metode analisis kualitatif. Kemudian diperoleh hasil bahwa adanya suatu kelalaian yang dilakukan oleh Perawat. Perbuatan Perawat termasuk kedalam perbuatan melawan hukum serta Perawat harus bertanggung jawab atas perbuatannya tersebut.